Investigation of the Effect of the Homogenization Regime on Energy Costs and Shelf Life of Yogurt with Dogberry Puree - Yuriy B. Gerber; Tatiana V. Kalinovskaya; Alexander V. Gavrilov; Natalia S. Kiyan (Инженерные технологии и системы)
Introduction. Homogenization is one of the most significant factors ensuring the successful implementation of the technology for manufacturing various dairy products. During this process, there are changed the properties and structure of proteins. In particular, there is decreased the size of casein micelles, which break down into submicells. After that, the accumulation of submicells on the surface of fat particles is likely. The increase in the homogenization pressure amplifies the mechanical effect on the particles, therefore, the average size of fat globules decreases. Aim of the Study. The study is aimed at reducing energy costs for manufacturing dairy products while ensuring the maximum preservation of the quality of dairy products. Materials and Methods. There has been studied the influence of homogenization pressure on the process technical parameters such as the power used for the homogenizer drive and for the dynamics of changes in the product properties during storage. The analytical dependences describing the main parameters of homogenization are considered. Results. Compliance with the recommended homogenization parameters and other parameters, in particular heat treatment, can significantly increase the product shelf life without significant changes in the initial quality indicators. If the process conditions allow crushing the initial fat particles to a size of about 1.0 micrometer and distributing them evenly throughout the volume, it makes possible to get a significant improvement in the taste and consistency of the resulting products. There has been studied influence of homogenization parameters on the shelf life of yogurt manufactured according to the proposed formula with using southern fruits, in particular, with dogberries. Discussion and Conclusion. Taking into account the results of experimental studies, we have concluded that the energy costs are significantly affected by the homogenization pressure (absolute value) and the ratio of pressure values at various stages of homogenization. The product manufactured according to the proposed formula with crushed dogberries preserves good taste, microbiological properties, and physical and chemical specified parameters for 14–15 days. It follows that the shelf life of yogurt manufactured according to the proposed formula should not exceed more than fourteen days at a temperature of no more than +6 °C.